2018
DOI: 10.1049/iet-pel.2017.0164
|View full text |Cite
|
Sign up to set email alerts
|

Novel multi‐terminal MMC‐based dc/dc converter for MVDC grid interconnection

Abstract: Multi-terminal modular multilevel converter (MMC)-based dc/dc converter with the medium-frequency ac-link transformer is an attractive and feasible solution for interconnecting medium-voltage direct-current (MVDC) grids. This study proposes a novel multi-terminal dc/dc converter which features significantly reduced number of components compared with the conventional converter topology. The proposed dc/dc converter is capable of interconnecting multiple MVDC grids with different voltage levels as well as contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…MVDC networks connecting multiple MVAC grids would provide voltage support, power quality, and flexibility [118]. Multiterminal systems can be extended to more readily than ring networks can and offer the ability to intertie multiple networks at one point [119,120]. The protection and control of multiterminal MVDC networks need further research and development due to the inherent instability of MTDC VSC-based systems [115].…”
Section: Grid Topologiesmentioning
confidence: 99%
“…MVDC networks connecting multiple MVAC grids would provide voltage support, power quality, and flexibility [118]. Multiterminal systems can be extended to more readily than ring networks can and offer the ability to intertie multiple networks at one point [119,120]. The protection and control of multiterminal MVDC networks need further research and development due to the inherent instability of MTDC VSC-based systems [115].…”
Section: Grid Topologiesmentioning
confidence: 99%
“…Medium-voltage dc and high-voltage dc grids have been the focus of many research studies recently regarding their increasing applications in rapidly growing grid-connected renewable energy systems, such as wind, solar and wave farms [10][11][12][13][14][15]. To connect dc renewable resources to the grid Voltage Sourced Converters (VSC) are used commonly [16].…”
Section: Medium-voltage Step Up DC / Dc Convertersmentioning
confidence: 99%
“…In the study [14], the power loss in the HVDC transmission line has been calculated and simulated in two models. Jafarishiadeh et al [15] suggested a novel dc/dc converter for linking multiple DC grids with various voltage levels while additionally controlling the power flow between them. In the study [16], HVDC links/bipolar connections were added in a power system to enhance the voltage profile.…”
Section: Introductionmentioning
confidence: 99%